THE USE OF EXPONENTIAL FUNCTION FOR ESTIMATION OF THE RETENTION RATE OF IUD - K. Mohammad; H. Malek-Afzali (Tehran University of Medical Sciences, 1979)
Due to the limitations of the "life table method" the exponential model was used to estimate the IUD termination and retention rate among 1,390 women. Since the conditional probability of IUD termination during the first month of insertion is considerably higher than the subsequent months, data relating to the first 30 days was considered separately. Furthermore a constant termination rate was assumed for the remaining period of observation. Comparison was made between the estimates obtained by our method and the results obtained from the life table method. In the majority of cases the difference between the estimates was in the third decimal figure.